Monetary policy, inflation and economic growth in Pakistan: Exploring the co-integration and causality relationships - Imran Sharif Chaudhry; Yasmeen Qamber; Fatima Farooq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This paper investigates the long run and short run relationships of monetary policy, inflation and economic growth in Pakistan using co-integration and causality analysis during the period 0f 1972-2010. A large number of empirical studies on the relationships of monetary policy and inflation are available and most of these have analyzed the effectiveness of monetary policy in controlling inflation in Pakistan. The present study fills the gap in the literature by analyzing the nexus of monetary policy, inflation and growth in Pakistan. The results indicate that credit to private sector, the variable of financial depth, real exchange rate and budget deficit are found elastic and significant variables to influence the real GDP in Pakistan. The pair-wise Granger Causality results suggest that real GDP and real exchange rate are causing to each other bi-directionally. The real GDP also do cause financial depth (M2GD), domestic credit (CREDIT) and budget deficit (BDEF) uni-directionally. The real exchange rate is also causing the financial depth and budget deficit variables. The results are consistent with the empirical literature.
Keywords: 330; Monetary Policy; Economic Growth; Inflation; Co-integration Analysis; Causality Analysis; Pakistan; Geldpolitik; Geldpolitische Transmission; Wirtschaftswachstum; Kointegration; Kausalanalyse; Pakistan